Enhanced Molybdenum Recovery Achieved by a Complex of Porous Material-Immobilized Surface-Engineered Yeast in Development of a Sustainable Biosorption Technology - Thiti Jittayasotorn; Kentaro Kojima; Audrey Stephanie; Kaho Nakamura; Hernando P. Bacosa; Kengo Kubota; Masanobu Kamitakahara; Chihiro Inoue; Mei-Fang Chien (Microorganisms)
Molybdenum (Mo) is a critical industrial metal valued for its corrosion resistance and strength-enhancing properties. However, increasing demand necessitates more efficient and sustainable recovery methods. Bio-recovery of Mo by biosorption is a promising resolution, especially by the use of surface-engineered microbes that express metal binding proteins on its cell surface. This study investigates the potential of Saccharomyces cerevisiae strain ScBp6, which displays a molybdate-binding protein (ModE) on its cell surface, immobilized on porous materials. Our findings reveal that polyurethane sponges (PS) significantly outperform ceramic materials in yeast immobilization, entrapping 1.76 × 107 cells per sponge compared to 1.70 × 106 cells per ceramic cube. Furthermore, the yeast–PS complex demonstrated superior Mo adsorption, reaching 2.16 pg Mo per yeast cell under 10 ppm Mo conditions, comparable to free yeast cells (1.96 pg Mo per yeast cell). These results establish PS as an effective and scalable platform for Mo recovery, offering high biosorption efficiency, reusability, and potential for industrial wastewater treatment applications.